State politics in India - Weiner, Myron (Princeton, New Jersey : Princeton University Press, 1968)
The essays in this book compare and analyze political processes in eight states within the Indian Union. A long introductory chapter by Myron Weiner sets the stage for individual studies of each state by separate scholars, namely: Myron Weiner (MIT) on Political Development in the Indian States; Paul H. Brass (University of Washington) on Uttar Pradesh; Wayne Wilcox (Columbia University) on Madhya Pradesh; Ram Joshi (S.I.E.S. College, Bombay) on Maharashtra; Balraj Puri (Editor, Kashmir Affairs) on Jammu and Kashmir Marcus F. Franda (Colgate University) on West Bengal; Lawrence L. Shrader (Mills College) on Rajasthan; Hugh Gray (University of London) on Andhra Pradesh; and Baldev Raj Nayar (McGill University) on Punjab. Originally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Political development in the Indian States / by M. Weiner --Uttar Pradesh / by P.R. Brass -- Madhya Pradesh / Wayne Wilcox -- Maharashtra / by Ram Joshi -- Jammu and Kashmir / by Balraj Puri -- West Bengal / by Marcus F. Franda -- Rajasthan / by Lawrence L. Sharader -- Andhra Pradesh / by Hugh Gray -- Punjab / by Baldve Raj Nayar.
Print versio record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: State governments -- India; Indic states -- Politics and government; POLITICAL SCIENCE -- Public Affairs & Administration; HISTORY -- Asia -- India & South Asia; State governments; India